The association between weight-adjusted waist index and respiratory symptoms in U.S adults: A national cross-sectional study - Yu Wang; Wenlu Chang; Yiwei Lu; Yi Xin; Ximing Li (PLoS ONE, 2025)
Objective This study aimed to evaluate the relationship between the weight-adjusted waist index (WWI) and respiratory symptoms, including cough, wheezing, and dyspnea, as well as the related respiratory diseases, namely chronic obstructive pulmonary disease (COPD) and asthma, in adults. Methods This cross-sectional study included 14,760 adults aged over 40 years, drawn from the National Health and Nutrition Examination Survey (NHANES) conducted between 2003 and 2012. Weighted logistic regression analysis was employed to investigate the association between WWI and respiratory symptoms, including cough, wheezing, and dyspnea, as well as related respiratory diseases such as COPD and asthma. Subgroup analyses and interaction tests were performed to stratify the data by age, gender, and race. Additionally, smooth curve fitting and threshold effect analyses were utilized to explore potential non-linear relationships between WWI and respiratory symptoms, as well as the associated respiratory diseases. Results After adjusting for covariates, a positive association was observed between WWI and respiratory symptoms, including cough, wheezing, and dyspnea [odds ratio (OR): 1.39, 95% confidence interval (CI): 1.29–1.50; OR: 1.62, 95% CI: 1.51–1.73; OR: 1.58, 95% CI: 1.50–1.67]. This association extended to related respiratory diseases such as COPD and asthma (OR: 1.42, 95% CI: 1.30–1.54; OR: 1.43, 95% CI: 1.33–1.54). Subgroup analyses indicated that the relationship between WWI and wheezing was modified by race, whereas dyspnea was influenced by age, gender, and race. For COPD, the association was affected by gender. Smoothed curve fitting revealed nonlinear, J-shaped associations between WWI and cough, COPD, and asthma (OR: 1.39, 95% CI: 1.29–1.50, P < 0.001; OR: 1.42, 95% CI: 1.30–1.54, P < 0.001; OR: 1.43, 95% CI: 1.33–1.54, P < 0.001). Furthermore, the breakpoint (K) was found to be 9.99 for both wheezing and dyspnea, with P < 0.05 for log-likelihood ratios in both instances. Conclusions This study provides evidence linking elevated levels of WWI to an increased risk of respiratory symptoms, including cough, wheezing, and dyspnea, as well as associated respiratory diseases such as COPD and asthma in U.S adults. These findings offer novel insights into the management of respiratory symptoms and diseases.